Effect of Weight Loss on Serum Osteocalcin and Its Association with Serum Adipokines - Mohammed S. Albadah (International Journal of Endocrinology, 2015)
Studies have suggested that osteocalcin, a bone formation marker, is related to body metabolism and insulin sensitivity. Whether this relation is mediated through an interaction with adipokines remains unclear. The aim of this study was to assess the effect of weight loss on serum osteocalcin and its relation with three adipokines, adiponectin, chemerin, and resistin. Forty-nine obese nondiabetic males completed a four-month dietary program. Body mass index (BMI) decreased significantly from 39.7±7.6 to 37.8±7.6 (P<0.001). This was associated with significant reduction in waist circumference, fasting blood glucose, HOMA-IR, total and LDL-cholesterol, bone-specific alkaline phosphatase (BAP), and resistin (P<0.05). There was significant increase in serum adiponectin and undercarboxylated osteocalcin (uOC) (P<0.001). The changes in uOC levels were negatively correlated with changes in serum triglycerides (r=-0.51, P<0.001) and positively correlated with changes in BAP (r=0.52, P<0.001). In contrast, the changes in uOC were not correlated with changes in BMI, waist circumference, fasting blood glucose, HOMA-IR, total and LDL-cholesterol, hsCRP, vitamin D, and circulating adipokines. We concluded that the increase in serum uOC following weight loss is not related to the changes in circulating adipokines levels.